Educational Values in The Arabic Imperatives (A Stylistic Analysis of the Qur’an) - M. Ircham (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aims to reveal the education values ​​in al-Qur’an through its stylistics (a linguistic aspect), such as imperative (al-amr). So far, the exploration of values ​​in al-Qur’an still has a lot to do with the substance of the verse. This study uses a stylistic analysis of al-Qur’an, which is descriptive and theoretical, with a literature approach. The results of this study include, first, the stylistics of al-Qur’an implies educational values ​​and explains how these values ​​are internalized. Second, the stylistics of al-Qur’an in imperative form (al-amr) contains educational values ​​that enable a person to become a better, more developed and mature human being. The education values meant here are obedience, affection and responsibility.